A security network in PSI photoprotection: regulation of photosynthetic control, NPQ and O2 photoreduction by cyclic electron flow - Chaux, Frédéric; Peltier, Gilles; Johnson, Xenie (Frontiers in Plant Science, 2015)
Cyclic Electron Flow (CEF) is a regulator of acceptor-side limitations and has multiple functions in the green alga, Chlamydomonas reinhardtii. Here we draw on recent and historic literature and concentrate on its role in Photosystem I (PSI) photoprotection, outlining causes and consequences of damage to PSI and CEF’s role as an avoidance mechanism. We outline two functions of CEF in PSI photoprotection that are both linked to trans-thylakoidal gradient formation and luminal acidification: firstly, its action on Photosystem II non-photochemical quenching and photosynthetic control and secondly, its action in stromal poising to overcome acceptor-side limitation by rebalancing NADPH and ATP ratios for carbon fixation.